Analisis Pengaruh Aliran Fluida Pendingin Dan Waktu Pengelasan Spot Welding Kw14-1031 Terhadap Kekuatan Tarik Pelat Baja ST 40 - Adiaksa, I Made Anom; I Nyoman Gede Suta Waisnawa; Ida Bagus Gde Widiantara; I Wayan Marlon Managi (Journal of Applied Mechanical Engineering and Green Technology, 2026)
Spot welding is greatly influenced by the cooling medium in terms of welding characteristics such as strength. The tensile strength of ST 40 steel plate welded joints is influenced by the cooling medium and welding time. Testing and data collection use experimental methods on spot welding machines and shear tests. Data collection uses quantitative methods while processing uses descriptive methods. The ASTM E8 standard is used in sample testing. The flow of coolant fluid in the spotwelding process significantly affects the HAZ diameter. Faster fluid flow increases heat transfer from the electrode to the coolant, keeping the electrode and weld material temperatures below 1,500 ºC, thereby reducing electrode wear and maintaining a stable weld nugget size at 5.00 mm. The lowest HAZ diameter was recorded at a flow rate of 5 liters/minute with a HAZ diameter of 8.30 mm, while the highest was at a flow rate of 2 liters/minute with a diameter of 10.43 mm. Too fast cooling or too short welding time can cause brittle weld joints and reduce tensile stress. Conversely, slower cooling with appropriate welding time produces optimal tensile strength while maintaining the structural integrity of the joint. Optimal results were found at a fluid flow rate of 2 liters/minute at 5.0 seconds with a tensile stress of 96.10 MPa, 3 liters/minute at 6.0 seconds with a tensile stress of 104.89 MPa, 4 liters/minute at 7.0 seconds with a tensile stress of 114.00 MPa and 5 liters/minute at 8.0 and 9.0 seconds with tensile stress of 116.72 MPa and 125.76 MPa.